Do changes in land use, water bodies, and grazing pastures have a detrimental influence on environmental quality? Opportunities and threats to long-term growth. (1st January 2023) - Khan, Imran; Lei, Hongdou; Muhammad, Ihsan; Khan, Ahmad; Lei, Mingyu
Abstract: Land use activities mainly for economic and agricultural purposes have converted one third to one half of our planet's land surface into urban expansion and agricultural practice, which has had significant impacts on natural ecosystems, food production, and environmental quality, attracting the attention of researchers and policymakers. Consequently, land use is emerging as a fundamental issue in global environmental change and sustainable development. This study represents an addition to the prevailing literature by investigating the asymmetric impacts of land-use and land-cover changes on environmental quality in Pakistan using time series data from 1961 to 2016. Carbon dioxide (CO2) emissions were deemed a dependent variable (a proxy for environmental quality), whereas built-up land, cropland, water bodies, and grazing land were considered independent. A nonlinear ARDL bound testing technique (NARDL) was used to investigate dynamic cointegration among the study variables. Moreover, this study used the BDS test and structural break unit root test to confirm nonlinearity and stationarity of the data set. The results confirm that the variables exhibit asymmetrical co-integration. There is a symmetric unidirectional causation, running from built-up land and grazing land towards CO2 emissions with coefficients of 10.570 and 17.045, respectively. Furthermore, asymmetric causality shows that any positive shocks to built-up land (6.134) and water bodies (20.335) significantly cause CO2 emissions. Similarly, a negative shock to grazing land (16.470) also causes CO2 emissions. By contrast, a neutral effect was found between cropland and CO2 emissions. Graphical abstract: Graphical abstract Image 1 Highlights: Asymmetric co-integration exists among the variables. A unidirectional symmetric causality exists, running from built-up land to CO2 emissions. A neutral effect was found between cropland and CO2 emission. Any negative shocks to grazing land considerably impact CO2 emission. From these findings, environmental policies are also discussed.